Forced Migration Governance: In Search of Sovereignty - Farahat, Anuscheh; Markard, Nora (German law journal, 2016)
The European Union (EU) Member States have experienced the recent refugee protection crisis in the EU as a de-facto loss of control over their borders. They find themselves unable to subject entry into their territory to a sovereign decision. In response, the Member States have sought to regain full sovereignty over matters of forced migration, both unilaterally and cooperatively, seeking to govern a phenomenon—forced migration—that by definition defies governance. Unilateral measures include forced migration caps and a search for ways to circumvent responsibility under the Dublin system. Cooperative efforts by EU Member States include the search for ways to more effectively govern forced migration at the EU level and beyond. Supranational EU efforts include the introduction of an internal relocation scheme and support for Italy and Greece in processing asylum claims in so-called “hotspots.” Beyond the EU, Member States are seeking to externalize protection responsibility to third world countries under international agreements, in particular, by returning asylum seekers to Turkey. This Article outlines the unilateral and cooperative governance efforts undertaken and shows that states' sovereign decisions over migration are significantly limited in the case of forced migrants, both by EU law and by international law.